Economics of Income Redistribution - Tullock, G. author. aut Link
IX, 222 p.
Keywords: While income redistribution is one of the most important functions of modern governments, the world has changed greatly since this first edition of Economics of Income Redistribution was published in 1983. Pension systems and medical programs are in a state of crisis in many parts of the world and the general political mood is shifting away from income redistribution. Economics of Income Redistribution (2nd edition) brings this work up to date by discussing the economic and political aspects of income redistribution. It examines the classical moral objective of redistribution to assist the poor, as well as income transfer for pensions, education and intra-family gift giving.